O76 Fix the fracture: how do you safely simulate orthopaedic theatre to a new demographic as part of a widening access initiative?. (5th November 2017) - McGrory, G; McCrossan, M; Paton, C
Abstract : Background/aims: There are documented barriers to work experience in medicine for children from low socio-economic backgrounds. This can adversely affect their chances of successfully obtaining a medical school place Academic ability is not the only factor medical school applicants should demonstrate, but they should also understand what a career in medicine involves NHS Lanarkshire currently provides a three-day in-hospital work experience programme to local schoolchildren. In order to provide further opportunities to experience medical careers first hand, a widening access simulation initiative has been developed. The emphasis is on exposure to simulated surgical activities in hands-on theatre environment, as this is challenging to access during traditional work experience programmes due to safety concerns for both schoolchildren and patients resulting in a passive observational experience. This work describes the evolution of 'Fix the Fracture', a simulated widening access orthopaedic theatre session. Project description: Creating a simulated orthopaedic theatre that is both safe for schoolchildren to gain hand-on experience yet provides an authentic surgical experience is challenging. Due to health and safety concerns, real orthopaedic equipment could not be used due to the likelihood of injury. The same issues arose when considering what material to best use to simulate broken bones, as training sessions with postgraduates had previously used broken animal bones, but again this poses a health and safety issue to schoolchildren. Results: We created an authentic theatre environment using basic surgical equipment and a simulation mannequin whose plastic legs had been replaced by legs filled with polyester and an open fracture created by inserting pre-broken plastic bones with pre-drilled holes. Moulage was used to create an open fracture skin effect. Surgical drapes were used to cover the leg for authenticity. The bones were repaired by the schoolchildren using a toy model construction system that consisted of reusable metal strips, plates and bolts. This minimised any risk of injury and providing the opportunity to 'repair' a fracture in an authentic orthopaedic theatre environment. Conclusions and recommendations: Using simulation in widening access is a novel approach to work experience supplementation, but is one where the only boundary is the imagination. This descriptive project has shown that there are low cost, reusable options to simulating theatre environments. This enables schoolchildren to get hands on theatre experience, augmenting their work experience and providing them with an inspirational and memorable experience to take forward to medical school applications and interviews. Reference: . Nicholls, G.